(untitled) - Maney, Kevin (Hoboken, NJ, 2003)
Praise for THE MAVERICK AND HIS MACHINE "Like all great biographers, Kevin Maney gives us an engaging story and so much more. His fascinating and definitive book about IBM's founder is replete with amazing revelations and character lessons that resonate today. Among the gems: how a demanding curmudgeon managed to shape a collaborative corporate culture-and create a legacy that changed the world." -Rosabeth Moss Kanter Harvard Business School, bestselling author of Evolve! and When Giants Learn to Dance "The gripping story of sky-high ambition, iron willpower, huge bet-the-company gambles, humiliating failure, and unparalleled success-one of the best books ever written about the technology industry, about one of the most fascinating people in twentieth-century America." -Marc Andreessen Cofounder of Opsware, Inc. and Netscape "The story of Watson and IBM is a compelling-and, at times, cautionary-tale of a determined, charismatic, flawed, and ultimately successful leader. Anyone interested in the story of business in America, the birth of high-tech, or simply the rags-to-riches tale of one determined businessman should read this book." -Robert M. Menschel Senior Director, Goldman Sachs author of Markets, Mobs, and Mayhem "In an action-packed story that reads like a novel, Kevin Maney paints a convincing portrait of a man who, having been a convicted criminal, redeemed himself and reshaped the American business landscape. The career of Thomas Watson, the effective founder of IBM, is not only fascinating, but offers many critical lessons on management and personal conduct that remain extremely poignant today."
Keywords: Computer industry,International business machines corporation,Businessmen; History,History,Biography; United states,United states